2021
DOI: 10.3390/foods10071569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Egg Yolk and Soybean Phospholipids on Hepatic Fatty Acid Profile and Liver Protection in Rats Fed a High-Fructose Diet

Abstract: Perturbed lipid metabolism leads to ectopic lipid accumulation in tissues, such as the liver, thereby causing nonalcoholic fatty liver disease (NAFLD) and negatively influencing circulating lipid profile-inducing dyslipidemia. Phospholipids (PLs) with special biological activity are used to treat chronic diseases such as cardiovascular and cerebrovascular disease. PLs derived from egg yolk and soya bean have significant antioxidant and lipid-lowering abilities. This study examined the therapeutic effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…These results suggest that the increased liver weights and macrovesicular fatty change of the hepatocytes in the HFrD group were caused by the accumulation of triglycerides in the liver. In other words, the daily consumption of excessive fructose for 4 weeks induced a typical NAFLD-like situation, as seen in other reports (12,33,34). In this study, periportal vacuolation in the hepatocytes was observed in the HFrD group after 4-weeks consumption (Table II).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggest that the increased liver weights and macrovesicular fatty change of the hepatocytes in the HFrD group were caused by the accumulation of triglycerides in the liver. In other words, the daily consumption of excessive fructose for 4 weeks induced a typical NAFLD-like situation, as seen in other reports (12,33,34). In this study, periportal vacuolation in the hepatocytes was observed in the HFrD group after 4-weeks consumption (Table II).…”
Section: Discussionsupporting
confidence: 87%
“…Rats on fructose but not glucosesupplemented diets displayed an abnormal glucose tolerance (11). Furthermore, excessive fructose intake has been widely used as metabolic syndrome-like animal models, including for obesity and diabetes animal models (12)(13)(14)(15). According to these studies, the daily consumption of diets high in fructose can rapidly produce all of the key features of the metabolic syndrome (16).…”
mentioning
confidence: 99%
“…HDL-C is an antiatherosclerotic lipoprotein that is synthesized primarily in the liver and can transport cholesterol from extrahepatic tissue to the liver ( Robertson et al, 2004 ). High serum TC concentrations can stimulate HDL-C transport, leading to transient high cholesterol accumulation in the liver ( Yin et al, 2021 ). Eight studies with 132 animals examined FFA levels after soybean treatment for NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…The various health benefits of eggs have been demonstrated in the existing literature, such as the improvement of blood lipids due to the intake of the phospholipids found in the egg yolk, the improvement of cognitive function due to the choline in the egg yolk [ 4 , 5 ], and increased bone density due to the calcium derived from the eggshells [ 6 ]. In addition, egg whites are characterized by their high dry weight protein content.…”
Section: Introductionmentioning
confidence: 99%